2020
DOI: 10.21608/esj.2020.25269.1126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Life (QoL) of Patients with Adolescent Idiopathic Scoliosis (AIS) after Surgical Correction

Abstract: The article does not contain information about medical device(s)/drug(s). No funds were received in support of this work. The authors report no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…No postoperative tilt reported among 18 [90.0%] and 2 [10.0%] had slight tilt. Abdelaziz et al [33] found that the surgical correction elicited a significant reduction in the Cobb's angle and pelvic tilt with significant increase in the lumbar lordosis reflecting the successful outcomes of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…No postoperative tilt reported among 18 [90.0%] and 2 [10.0%] had slight tilt. Abdelaziz et al [33] found that the surgical correction elicited a significant reduction in the Cobb's angle and pelvic tilt with significant increase in the lumbar lordosis reflecting the successful outcomes of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study published by Herdea et al demonstrated that there are statistically significant correlations between the correction rate and improvements in SRS scores ( P < 0.001), both in terms of the overall score and within each individual domain of the survey. The conclusion drawn from these findings is that achieving a higher correction rate leads to increased values in the SRS score [ 20 ]. In another study conducted by Ng Bobby , it was further demonstrated that the degree of curve rectification after surgery and the preoperative maximum Cobb angle serve as significant predictors of various outcomes, such as function scores, self-image, and satisfaction with management in AIS patients.…”
Section: Discussionmentioning
confidence: 99%